PENGARUH KEMAMPUAN BERPIKIR KRITIS DAN GAYA BELAJAR TERHADAP HASIL BELAJAR - Dian Aditya; Eko Suyanto; Viyanti - (Jurnal Pembelajaran Fisika, 2013)
Every student has the different of critical thinking skill, there are more quick to crtiticize the subject matter and there are difficulties. As well as learning styles, every student has the different of learning styles. Different of critical thinking skill and learning styles result some of the students felt can’t to problems solve on learning process.This research aims to know about (1)influence of the critical thinking skill on learning outcomes of inquiry role approach learning (2)influence of learning styles on learning outcmoes of inquiry role approach learning. Learning outcomes in this research is cognitive aspect.This research was implemented at Senior High School State 1 Pesisir Selatan West Lampung District, using the experimental class (XI IPA 2) with sample are 37 students. Learning process using inquiry role approach learning. Learning outcomes obtained from test results Based on the analysis of the data concluded that:(1) Has an influence critical thinking skill for learning outcomes with inquiry role approach learning.(2)Has an influence learning styles for learning outcomes with inquiry role approach learning.Keyword: critical thinking skill, learning styles, inquiry role approach, and leraning outcomes.